State of wonder - Patchett, Ann. (Harper, 2011)
A researcher at a pharmaceutical company, Marina Singh journeys into the heart of the Amazonian delta to check on a field team that has been silent for two years--a dangerous assignment that forces Marina to confront the ghosts of her past.